2021
DOI: 10.3389/fpls.2021.615019
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Removal by Grain in Modern Soybean Varieties

Abstract: Knowing the nutrient removal by soybean grain harvest in different varieties, locations, and over time is essential to correctly adjust agronomic recommendations, update farmers’ practices, and increase nutrient use efficiency. A field-based research trial was carried out to assess macronutrients [nitrogen (N), phosphorus (P), potassium (K), magnesium (Mg), calcium (Ca), and sulfur (S)] removed in grain by modern soybean varieties from southern Brazil introduced between 2007 and 2016. We examined changes betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…In the research conducted by Neto et al (2017) 77 , the micronutrient content of soybeans were not signi cant under S fertilization. In the study of Sohrabi et al…”
Section: Content Of Macro-and Micronutrients Of Soybean Under Phospho...mentioning
confidence: 83%
“…In the research conducted by Neto et al (2017) 77 , the micronutrient content of soybeans were not signi cant under S fertilization. In the study of Sohrabi et al…”
Section: Content Of Macro-and Micronutrients Of Soybean Under Phospho...mentioning
confidence: 83%
“…There is undeniable an effort in the breeding programs to select genotypes with higher yields than those already grown today. However, some gaps also need to be addressed by breeders, especially regarding traits of interest to the industry (oil and protein contents) 4 , uptake of nutrients by genotypes in Brazilian Cerrado 5 , besides seeking to increase grain yields 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Soybeans have a high K requirement; on average, the rate of K extraction by the plants is around 42 to 48 kg of K for the production of one ton of grain [10,13]. Therefore, large quantities of K are required by soybean plants since this crop is highly sensitive to K deficiency [14], especially the modern high-yield soybean genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, large quantities of K are required by soybean plants since this crop is highly sensitive to K deficiency [14], especially the modern high-yield soybean genotypes. Indeed, Esper-Neto et al [13] reported that the amount of K removed by modern soybean genotypes was 21% to 45% higher compared with soybean genotypes historically planted in Brazil during the 20th century. The K deficiency limits plant development and the grain yield of soybeans by negatively affecting vital plant processes such as water status, cellular turgidity, protein synthesis, assimilate transport, cell expansion, and enzyme activation [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation